Identification and Characterization of Isocitrate Lyase Genes in Amaranthus caudatus L. - Hadi, Saba; Habh, Asseel M. M.; Yousif, Alyaa Muhsin (Contemporary Research and Perspectives in Biological Science Vol. 11, 2025)
Background: Isocitrate lyase is considered an enzymatic indicator of the cycle diagram and occupies different functions in the plant cell metabolism. Isocitrate lyase (EC 4.1.3.1) catalyzes the reaction isocitrate < glyoxylate + succinate and has been reported to be widely distributed. Objective: The objective of this study was to identify Isocitrate lyase genes and to develop the specific primers. Methods: Research materials in this work were obtained and worked at the State University of Varonish, Russia, for the period from 2017 to 2018. Using primers prefixes cloned of metamorphic genes Isocitratase lyase, that were able to find the presence of two genes within the gene of Amaranthus, namely (icl1, icl2), which are mentioned later in the relay’s products by the polymerase chain reaction (PCR). Results: The results of this study showed the total RNA extract contained two types of mRNA of Isocitrate lyase genes of the A. thaliana genes named ICl2 and ICl1. The presence of two genes, ICL1 and ICL2, in the Amaranthus genome showed that the fragment of the ICL1 gene of Arabidopsis was 53% fragmented, the ICL2 gene is 447 bp long, and its homology with the ICL1 gene of Arabidopsis was 36%. On the basis of sequences specific to isocitrate lyase genes, which made it possible to investigate their expression activity at the initial stages of Amaranthus development. Conclusion: The results of this study concluded that the total RNA extract contains two types of mRNA of Isocitrate lyase genes, shown in their symmetry with A. thaliana genes ICL2 and ICL1.